2017
DOI: 10.1073/pnas.1615585114
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural characterization of oxygen-sensitive 2-thiouridine synthesis catalyzed by an iron-sulfur protein TtuA

Abstract: Two-thiouridine (s 2 U) at position 54 of transfer RNA (tRNA) is a posttranscriptional modification that enables thermophilic bacteria to survive in high-temperature environments. s 2 U is produced by the combined action of two proteins, 2-thiouridine synthetase TtuA and 2-thiouridine synthesis sulfur carrier protein TtuB, which act as a sulfur (S) transfer enzyme and a ubiquitin-like S donor, respectively. Despite the accumulation of biochemical data in vivo, the enzymatic activity by TtuA/TtuB has rarely bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…2a). The manner of interactions between TtuA and Fe-S (i.e., TtuA coordinately bound to Fe-S via three cysteine residues) was identical to that for holo-TtuA reported previously 10 . However, a new interaction directly coordinated between the unique Fe site of the [4Fe-4S] cluster and the C-terminus of TtuB was observed (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…2a). The manner of interactions between TtuA and Fe-S (i.e., TtuA coordinately bound to Fe-S via three cysteine residues) was identical to that for holo-TtuA reported previously 10 . However, a new interaction directly coordinated between the unique Fe site of the [4Fe-4S] cluster and the C-terminus of TtuB was observed (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Examples include: TtuA, which catalyzes the formation of 2-thioribothymidin (s 2 T) at position 54 (refs. 10,11 ); TtcA, which catalyzes the formation of 2-thiocytidine (s 2 C) at position 32 (ref. 12 ); and ThiI, which catalyzes the formation of 4-thiouridine (s 4 U) at position 8 (ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the timing of thioamide formation in the 6TG pathway was unknown, all enzyme assays were performed in parallel with an umber of potential precursors:g uanine (2), guanosine (3), guanosine monophosphate (GMP, 4), guanosine diphosphate (GDP, 5), and guanosine triphosphate (GTP, 6;F igure 2A). Since inorganic sulfide has previously been shown to function as as ulfur source for AANH enzymes in vitro, [9] we added lithium sulfide to the reaction mixtures and product formation was monitored by HPLC.H owever, none of the substrates were converted into the corresponding thioamide;arepresentative trace with 4 is displayed in Figure 2B.…”
mentioning
confidence: 99%
“…Although product peaks were not observed in the HPLC profiles of reactions with guanine and guanosine,n ew peaks with aU Vabsorbance at 340 nm, which is characteristic for 6TG,w ere formed in assays with each of the three tested guanine nucleotides ( Figure 2F). By comparison with synthetic references (Figure S4), we identified these new compounds as the corresponding thioamides, 6-thio GMP (6TGMP, 8, Figure 2G), 6-thio GDP (6TGDP, 9), and 6-thio GTP (6TGTP, 10). Additionally,b yu sing LC-HMRS we unequivocally confirmed that the new compounds are the expected thioamides.D ata for the formation of 8 is presented in Figures S5-6.…”
mentioning
confidence: 99%